2009
DOI: 10.1007/s11104-009-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous nitric oxide improves antioxidative capacity and reduces auxin degradation in roots of Medicago truncatula seedlings under cadmium stress

Abstract: The effects of nitric oxide (NO) on cadmium toxicity in Medicago truncatula seedlings were studied by investigating root growth and uptake of antioxidants, IAA and ions. Exposure to cadmium reduced root growth and NO accumulation, and increased the production of reactive oxygen species (ROS) in roots. Supplementation with NO improved root growth and reduced ROS accumulation in roots. The NO-scavenger cPTIO, the nitrate reductase (NR) inhibitor tungstate, and the NO synthase (NOS) inhibitor L-NAME all inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
124
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(145 citation statements)
references
References 44 publications
17
124
1
3
Order By: Relevance
“…maintained under salt stress conditions also showed decreased Ca 2+ content (Niaz & Rasul, 1998) in high salinity conditions. Salinity can also affect K + absorption and transport in plants (Shabala & Cuin, 2008;Xu et al, 2010). In the present study, the decreases in K + content compared to the controls probably occurred as a consequence of the antagonistic relationship between same-charged ions, as well as the competition between Na + and K + during nutrient absorption (Niaz & Rasul, 1998;Niu et al, 1995).…”
Section: Discussionmentioning
confidence: 53%
“…maintained under salt stress conditions also showed decreased Ca 2+ content (Niaz & Rasul, 1998) in high salinity conditions. Salinity can also affect K + absorption and transport in plants (Shabala & Cuin, 2008;Xu et al, 2010). In the present study, the decreases in K + content compared to the controls probably occurred as a consequence of the antagonistic relationship between same-charged ions, as well as the competition between Na + and K + during nutrient absorption (Niaz & Rasul, 1998;Niu et al, 1995).…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, our data also indicate that NO can modulate auxin metabolism and/ or transport, and thereby auxin signaling, in tomato cotyledons. This NO-auxin interaction has been reported in other systems and physiological events (Xu et al, 2010;Fernández-Marcos et al, 2011;Terrile et al, 2012). Although the exact mechanisms through which NO and auxin interact in plants still deserve further elucidation, the fact that NO has been shown to promote auxin-dependent gene expression via posttranslational modifications of the Arabidopsis auxin receptor protein TRANSPORT INHIBITOR RESPONSE1 is of particular note (Terrile et al, 2012).…”
Section: No Interconnects Light and Plant Hormones During Seedling Grmentioning
confidence: 77%
“…Xu et al [68] found that exogenous NO supply improved the antioxidative capacity and reduced the degradation of AUX in roots of Medicago truncatula seedlings exposed to Cd stress. In another study, it was noted that NO acts downstream of AUX on modulating root architecture in Arabidopsis seedlings exposed to Cd stress [69].…”
Section: No-phytohormone Cross Talk Under Heavy Metals Stressmentioning
confidence: 99%